El Partido Unión Revolucionaria y su proyecto totalitario-fascista. Perú 1933-1936 - Molinari Morales, Tirso (2006)
This study presents the central characteristics of a Fascist Party in Peru, its organization, ideology and political meaning for Latin America in the decade of the 1930s. The author examines it and analyzes the Revolutionary Union Party and the process of the formation of the conservative and charismatic populism of a political movement led by Luis M. Sanchez Cerro: a military man whose dictatorial government evolved into what one could identify as «bonapartism», because of its special authoritarian-populist character. Under this panorama we will present the essential historical evidence of the Fascist presence of that party, its complex relationship with political power, its ideological and corporative axes, its xenophobia with regard to Asian immigration, its organization, especially their black shirts, and the totalitarian character of their political project between 1933 and 1936